Yoshlarni manaviyati shakllanishida mahallaning o’rni - Berkinov Oybek Toxir o’g’li, Xujamkulov Xurshid Artikboyevich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
Always having peace in the family, actively organizing free time, organizing family trips to places of culture and art serve to ensure family harmony. One of the main conditions for proper upbringing of a child in the family is unity in education. The issue of education is complex, and it is important to carry out such a hugely responsible and honorable work in cooperation with the family, neighborhood, school and the general public.